ASSOCIATION OF SERUM TESTOSTERONE AND SEX HORMONE BINDING GLOBULIN LEVELS IN FEMALES WITH ACNE BASED ON ITS SEVERITY - Kiayani, Asma Javed; Rehman, Farid -ur- (Journal of Ayub Medical College Abbottabad, 2016)
Background: Androgens are involved in the development of acne. The aim of this study was to find out if there was an association of serum testosterone and sex hormone binding globulin (SHBG) in females with acne based on its severity. Methods: It was a cross sectional study, conducted in Dermatology unit of Fauji Foundation Hospital (FFH), Rawalpindi. Duration of study was eight months. Adult females with acne were enrolled in the study. Patients were categorized into minor, mild, moderate groups. Blood samples were taken for serum testosterone and SHBG. Results: Five hundred and thirty-one adult female were enrolled into the study. The mean age was 21.49±4.73 years. Acne was graded as minor in 78 (14.7%) cases, mild in 248 (46.7%) and moderate in 205 (38.6%). There was no statistically significant relationship between the levels of serum testosterone (p=0.776) and SHBG (p=0.711) with acne severity. Conclusion: There was no association of serum testosterone and sex hormone binding globulin levels in females with acne based on its severity. Keywords: Acne, Sex hormone binding globulin, Testosterone